Extrastriatal dopaminergic changes in Parkinson's disease patients with impulse control disorders. Issue 1 (10th September 2013) - Lee, Jee-Young; Seo, Seong Ho; Kim, Yu Kyeong; Yoo, Hye Bin; Kim, Young Eun; Song, In Chan; Lee, Jae Sung; Jeon, Beom S
Abstract : Objective: To investigate the extrastriatal dopaminergic neural changes in relation to the medication-related impulse control disorders (ICD) in Parkinson's disease (PD). Method: A total of 31 subjects (11 and 11 drug-treated PD patients with and without medication-related ICDs and 9 healthy controls) having no other co-morbid psychiatric disorders participated in this study. Each subject underwent dynamic N -(3-[ 18 F]fluoropropyl)-2-carbomethoxy-3-(4-iodophenyl) nortropane (FP-CIT) positron emission tomography scans. Binding potentials (BP) at nucleus accumbens, amygdala, orbitofrontal and ventromedial prefrontal cortex (VMPFC), putamen and caudate nucleus were estimated, and whole brain parametric maps of [ 18 F]-FP-CIT binding were analysed by original and putaminal normalised manners. Results: Compared with the healthy controls, BPs at both VMPFCs were significantly high and the extrastriatal to putaminal BP ratios at all regions were approximately three times higher in both PD groups. The PD ICD patients showed significantly higher BPs at the right VMPFC and tendency to lower BPs at the left nucleus accumbens compared with those free of ICD. The ICD subjects also showed reduced uptakes at both ventral striatal regions in the original parametric analysis and higher uptakes at the left insular and right posterior cingulate cortex and lower uptakes at both ventral pallidums in the putaminal normalised parametric analysis compared with the non-ICD subjects. Conclusions: A great gap in extrastriatal versus striatal dopaminergic fibre degenerations is an intrinsic condition predisposing to ICD in PD. Distinct pattern of extrastriatal changes between the ICD and non-ICD patients could provide a further insight into a mechanism of ICD in PD.